PENGARUH KECERDASAN INTELEKTUAL DAN KECERDASAN SPIRITUAL DALAM MENDETEKSI FRAUD - Harun Alrasyid; Rahmawati Rahmawati; Rahmad Solling Hamid (Politeknik Keuangan Negara STAN, 2021)
This research aims to find out the influence of intellectual intelligence and spiritual intelligence in detecting Fraud. The study was conducted at the office of the Inspectorate of The Luwu Kingdom. There were 89 respondents as samples in this study using sampling techniques in the form of saturated sampling methods or censuses. Method of retrieving data using questionnaires. Data analysis techniques use multiple linear regression analysis analysis with Statistical Packages for Social Science (SPSS). The results found that the entire hypothesis in the study had been significantly proven. This means that intellectual intelligence and spiritual intelligence have a positive and significant effect in detecting Fraud.